Effect of Calcination Temperature on the Alumina-Zirconia Nanostructures Prepared by Combustion Synthesis - M. Jafar Tafreshi; M. Fazli; Z. Jafari Ayoub (Journal of Nanostructures, 2012)
In this research, a sol gel autocaombustion route has been proposed to synthesize alumina-zirconia composite powders, using ammonium bicarbonate as a new fuel. Then the effect of calcination temperature on phase transformation and crystallite sizes was investigated. To characterize the products XRD, TEM and BET analyses were used. XRD patterns of as-synthesized powder and calcined powders at 1100 ◦C and 1200 ◦C showed t-ZrO2 phase with small crystallite sizes (sintered at 1300 ◦C and the particle sizes after calcination were 14.90 nm and 50 nm for ZrO2 and Al2O3 phases, respectively as calculated from XRD and the transformation of t-ZrO2 to m-ZrO2 started at 1300 ◦C. TEM micrograph of as-synthesized powder revealed nanosize spherical particles of about 8 nm.